Enantioselective N‐Heterocyclic Carbene Catalysis that Exploits Imine Umpolung. (14th February 2019) - Fernando, Jared E. M.; Nakano, Yuji; Zhang, Changhe; Lupton, David W.
Abstract: The catalytic umpolung of imines remains an underdeveloped approach to reaction discovery. Herein we report an enantioselective aza‐Stetter reaction that proceeds via imine umpolung using N‐heterocyclic carbene catalysis. The reaction proceeds with high levels of enantioselectivity (all ≥96:4 er) and good generality (21 examples). Mechanistic studies are reported and are consistent with turnover‐limiting addition of the NHC to the imine. Abstract : Die Umpolung von Iminen ist ein wenig erforschter Bereich der enantioselektiven Katalyse. N‐heterocyclische Carbene (NHCs) wurden zur Katalyse einer enantioselektiven Aza‐Stetter‐Reaktion verwendet. Im Gegensatz zu Acyl‐Umpolung mit NHCs erfordert diese Reaktion stark nukleophile Katalysatoren. Die Reaktion ist enantioselektiv (≥96:4 er) und kann mit verschiedenartigen Iminen und 3‐Methylenchroman‐2‐onen durchgeführt werden.